Exploring investment behavior of women entrepreneur: Some future directions - Umair Baig; Batool Muhammad Hussain; Vida Davidaviciene; Ieva Meidute-Kavaliauskiene (International Journal of Financial Studies, 2021)
This study aims to explore the investment behavior of female entrepreneurs as the new competitor in the investment field and to determine the underlying factors that influence their investment attitudes. A qualitative investigation approach was employed for the study that includes 18 in-depth exploratory interviews to ascertain the fundamental determinants of the investment behavior represented by female entrepreneurs, an emergent section in investment. The accumulated data was analyzed through manual coding procedures. The study revealed that female entrepreneurs are not inclined to take risk in their business for investment decisions, they are somewhat conservative and risk averse. This research also asserts that if they spend quality time and get better training about the nuances of different investment tools, so they will also take risks in investment activities. Two big cosmopolitan cities Karachi and Lahore in Pakistan were selected as sample for this study. Research in other countries considering the culture and ethnicity must be conducted to expand the scope of understanding the investment behaviors of female entrepreneurs. This study outcomes would help the investment manager to understand women's psychology to develop significant portfolio recommendations, service providers to develop consultancy training centers, policy makers to mitigate their risk and maximize their return opportunities. Hence, intending to provide opportunities for gender equalities, this research appears to be the first in Pakistan to adopt the inductive approach in this domain.
Keywords: 330; financial decision-making; investment behavior; qualitative research; women entrepreneurs